Analysis of Income and Profits of Vegetable Traders in the Bersehati Market, Manado City - Pakaya, Angelita; B. Kalangi, Josep; D. Tolosang, Krest (PT FORMOSA CENDEKIA GLOBAL, 2024)
Indonesia is a developing country with certain industries that drive economic expansion. Located between two continents and the Asian continent, Indonesia occupies another strategic area and the Australian continent benefits Indonesia in its trade sector because Indonesia is a world trade traffic route. The author's research uses primary data, namely details collected or obtained directly by researchers or related parties in the field. To obtain primary data, you can use data collection techniques such as opinion polls, surveys, interviews, distributing questionnaires, focused discussions and observation. The findings of this study indicate that vegetable traders at the Bershati Manado Market earn a fairly high and stable average income from their sales. And the ratio between income and total costs incurred by traders is >1 so that the business experiences a profit.